Creating the florentine state : peasants and rebellion, 1348-1434 - Cohn, Samuel Kline (Cambridge University Press, 1999)
"This book offers a new approach to the study of the political history of the Renaissance: its analysis of government is embedded in the context of geography and social conflict. Instead of the usual institutional history, it examines the Florentine state from the mountainous periphery - a periphery both of geography and class - where Florence met its most strenuous opposition to territorial incorporation." "Yet, far from being acted upon, Florence's highlanders were instrumental in changing the attitudes of the Florentine ruling class."--Jacket